Implementasi Smart Farming Berbasis Internet of Things dan Tenaga Surya untuk Peningkatan Kualitas Pertanian Melon - Ahmad Heru Mujianto; Basuki; Imam Sopingi; Danang Rifqi Amrulli; Kamil Fatur Rahman (Jurnal Pemberdayaan Masyarakat, 2025)
The community service program in Sumbersari Village, Megaluh District, Jombang Regency aimed to enhance melon farming productivity and quality through IoT-based smart farming supported by solar energy. Activities included surveys, socialization, development of a monitoring application and hydroponic greenhouse, training in melon cultivation, and installation of IoT systems and solar panels for automatic irrigation and real-time monitoring. The results showed that farmers understood the basics of IoT, sensor use, and solar panel operation. Evaluation using a Likert scale (1–4) indicated most participants scored 3 (understand/agree) and 4 (strongly understand/strongly agree), reflecting significant improvements in knowledge and skills, categorized as good to very good. This program not only increased time and labor efficiency but also improved potential yields, supporting sustainable and technology-driven agriculture in rural communities.